Psychosocial Screening in Adult Burns Inpatients within a Scottish Burns Unit - Dawn Lindsay; Kim Kirkwood; Rebecca Crawford (MDPI AG, 2023)
National Burns Care Standards (NBCS) within the UK recommend psychological care throughout the burn pathway and psychosocial screening of inpatients admitted for over 24 h, at a time when this is clinically appropriate and prior to discharge. This brief report presents preliminary data from an audit of psychosocial screening in adult burns inpatients within a Scottish Burns Unit over a three-year period. Results are reported on the frequency and type of psychosocial screening completed. Differences between the groups of inpatients who were screened and those not screened are presented and discussed with a focus on plans for increasing the number of inpatients screened and improvements in how psychosocial screening data is collected.